Mekanisme dan kendala pemungutan Pajak Restoran (Studi pada Badan Pendapatan Daerah Kabupaten Sumba Timur) - Rohi, Dwiner Alfian; Kusumowati, Dewi (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2022)
This study aims to find out how to calculate the amount of restaurant tax at the Regional Revenue Agency of East Sumba Regency, to find out the procedure and process of collecting restaurant taxes at the Regional Revenue Agency of East Sumba Regency, to find out the obstacles faced by the Regional Revenue Agency of East Sumba Regency in the tax collection process. restaurants, and to find out the efforts of the Regional Revenue Agency in minimizing problems that arise in the process of collecting restaurant taxes. to find out the obstacles faced by the Regional Revenue Agency of East Sumba Regency in the process of collecting restaurant taxes. In this study, the types of data used are qualitative and quantitative data types. The data sources used are primary data and secondary data, in the form of target data and realization of restaurant tax revenues, profile data of the Regional Revenue Agency, and data on procedures and constraints in the restaurant tax collection process. For data collection techniques through interviews and documentation. From the results of the study it can be concluded that the way to calculate the restaurant tax is by multiplying the rate set by the government with the turnover obtained by the restaurant. The procedure or payment process consists of 4 stages, namely registration, determination, deposit, and billing. There are several obstacles in the restaurant tax collection process, including: taxpayers do not tell the actual turnover, taxpayers do not want to use the bill printed by the Regional Revenue Agency, taxpayers do not want to pay taxes on the pretext of not collecting taxes from consumers, in general taxpayer awareness to pay taxes is still very low. In minimizing these obstacles, the Regional Revenue Agency made several efforts such as conducting socialization to increase awareness of taxpayers in paying taxes, improving services and facilitating facilities in the tax payment process, providing strict sanctions for late paying taxes.